Smokeless tobacco industry's brand stretching through FM radio: A study from Delhi National Capital Region, India - Singh, Prashant Kumar; Jain, Rupal; Tyagi, Akansha; Yadav, Amit; Singh, Shalini (Frontiers in Public Health, 2022)
Smokeless tobacco (SLT) use is associated with multiple adverse health effects and mortality, with the highest burden in India. The WHO FCTC has banned tobacco advertisement, promotion and sponsorship via Article 13. Indian laws also prohibit any kind of direct or indirect advertisements in all forms of audio, visual and print media, brand promotion and sponsorship of tobacco products. However, tobacco industry continues to find aggressive marketing ways to advertise its products. This study aims to understand the extent of surrogate advertisement of SLT products through Frequency Modulation (FM) radio stations in the city of Delhi, India. In this study, the advertisements broadcasted over FM radio across different channels (private and government owned) in total 162 hours were analysed. The time duration was spread evenly over morning peak hours, off hours and evening peak hours. It was found that multiple brands including Vimal, Kamla Pasand, and Rajshree have used surrogate advertising to market their brands that are commonly associated with SLT products. However, no such advertisement was found to be aired on government owned FM channels. The total surrogate advertisements broadcasted were over 286 times where no significant difference was found in distribution among peak and non-peak hours. Study indicated that the tobacco industry is making its way to sell the products through indirect advertisements. The is a need not only to enforce the tobacco advertising ban laws in all forms of advertising media but also to strictly regulate SLT products.